Resolusi Konflik Pertanahan di Kelurahan Bara-baraya Kecamatan Makassar, Kota Makassar - Ahmad Adriadi; Firdaus W Suhaeb; Ridwan Said Ahmad (Universitas Negeri Makassar, 2023)
ABSTRACT This study aims to determine the background of the causes of land conflicts in Bara-baraya Village, Makassar District, Makassar City and how are the efforts that have been made in efforts to resolve land conflicts that occurred in the Bara-baraya area using Ralf Dharendrof's conflict theory and Henri Lefebvre's spatial dialectical approach. This type of research is descriptive qualitative research with the basis of phenomenological research. The data collection methods used are observation, interviews and documentation related to the problem to be raised. Data collection was carried out by purvose sampling technique, with the characteristics of the informants, namely representatives of the parties involved in the conflict.The results of this study indicate that, the background to the occurrence of land conflicts in the Bara-Baraya sub-district are (a) The existence of land claims by residents which led to the threat of eviction against Bara-baraya residents by Nurdin Dg Nombong together with Kodam XIV Hasanudin and Bara-baraya residents responded to this by conducting confrontations so as to form latent conflicts and manifest conflicts with the authority roles of various actors involved in the conflict. (2) As for what has been done as an effort to resolve the conflict, namely mediation by the South Sulawesi Provincial DPRD, consolation by the Indonesian National Human Rights Commission and the President of the Republic of Indonesia, as well as the trial pathway, namely the Makassar District Court, Makassar High Court and the Supreme Court of the Republic of Indonesia